The Abject Rogue: Satire, Social Critique, and Imperial Ambiguities in Tobias Smollett’s Roderick Random - Rasus Budhyono; Randy Ridwansyah; Budi Rukhyana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2026)
In Tobias Smollett’s Roderick Random (1748), the eponymous picaresque protagonist embarks on wanderings across regional, national, transatlantic, and social boundaries. Conveyed through a first-person narrative that blends satirical and picaresque aesthetics, the novel presents the worldview of a Scottish-born young man exposed to the vicissitudes of life during the period when the newly amalgamated United Kingdom was forging its path toward becoming a global empire. Rather than examining the novel’s historical impact on the social ailments of the eighteenth century that it satirizes, this article explores how the text constructs a literary imagination of a British Empire in the making. The protagonist’s role as an itinerant rogue grants him the narrative mobility necessary to expose aspects of eighteenth-century life that become targets of satire. By combining theories of satire, the picaresque, and abjection, this study argues that the novel’s narrative design both critiques and participates in the shaping of imperial ideology. Drawing on Edward Said’s contrapuntal reading method and Suvir Kaul’s postcolonial perspective, this article seeks to enrich discussions of the British Empire's fictional imagination. While existing scholarship has largely focused on the height of empire in the nineteenth century and its subsequent decline, this study returns to the mid-eighteenth century, when the vision and foundations of global empire were still being forged. The article argues that the novel reveals an ironic double stance toward colonial exploitation. While Roderick’s eventual rise to wealth and social status depends entirely on the plantation economy, the narrative remains silent about transatlantic slavery as the source of that fortune. This whitewashing of colonial violence exposes the deep moral ambiguities embedded in mid-century British expansion.